African and American Selves : ‘Contact Zones’ in All Our Names by Dinaw Mengestu - (:unkn) unknown (My University, 2017)
Dinaw Mengestu's recent novels about African migrants in the U.S. contribute to black fiction created out of an American experience. His third novel, All Our Names (2014), is a double narrative that alternates between post-independence Uganda and post-Civil Rights America, thus offering a critique on both postcolonial Africa and multiracial America. It gives voice to both a restless African man who seeks refuge in the U.S. and to an American social worker, Helen--a white Midwesterner, stuck in her hometown. We will examine how Mengestu constructs his two characters and weaves together their painful singular stories as parallel subjective first-person narratives that offer two different perspectives on Africanness and Blackness, and how he uses their encounter (a secret interracial love affair) to point at the contrasts and similarities of their two separate worlds and thus expose the instability of identity, the sense of self that affects both characters, beyond their differences.
Keywords: African Research